2019
DOI: 10.1080/25765299.2019.1607995
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun porous bio-fibre mat based on polylactide/natural fibre particles

Abstract: A fully bio-based highly porous bio-fibre mat from polylactide (PLA) and bagasse particles (BCp) composite have been investigated for scaffold applications. PLA and BCp were mixed in varying proportions in dichloromethane (DCM) and electrospun (with specific machine parameters) into fibres at varying spin angles (30 , 45 and 90). A constant weight fraction of BCp (5 wt. %) was used to form solutions with varying concentrations 0.09-0.14 g/ml which were then electrospun into fibres. Mechanical, moisture resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…This composite possesses the lowest crystallinity (65.1%) as shown in Table 1. This was also observed in the work of [9] where the low crystallinity was attributed to the presence of cold crystallization. The melting peak for PLA/CH (5 wt.%) and neat PLA is the same (159°C); PLA/CHS (10 wt.%) and PLA/CH (2.5 wt.%)/CHS (2.5 wt.%) have their melting peak at 152°C while that of PLA/CHS (5 wt.%), PLA/CH (10 wt.%) and PLA/CHS (wt.%)/CH (5 wt.%) occurred at 165°C, 169°C and 149°C respectively.…”
Section: Decomposition Characteristics Of Pla Fibre Compositessupporting
confidence: 70%
See 1 more Smart Citation
“…This composite possesses the lowest crystallinity (65.1%) as shown in Table 1. This was also observed in the work of [9] where the low crystallinity was attributed to the presence of cold crystallization. The melting peak for PLA/CH (5 wt.%) and neat PLA is the same (159°C); PLA/CHS (10 wt.%) and PLA/CH (2.5 wt.%)/CHS (2.5 wt.%) have their melting peak at 152°C while that of PLA/CHS (5 wt.%), PLA/CH (10 wt.%) and PLA/CHS (wt.%)/CH (5 wt.%) occurred at 165°C, 169°C and 149°C respectively.…”
Section: Decomposition Characteristics Of Pla Fibre Compositessupporting
confidence: 70%
“…Although electrospinning is a simple and quick method in the fabrication of nano-fibrous scaffolds, there still exist challenges in the fabrication of scaffolds with complex structures, such as the homogeneous distribution of pores, thus limiting its application in biomedicine. In the study, [9] observed that the addition of particles can lead to the formation of a porous fibre network, which enables the material to absorb water and solvents. The introduction of new biopolymers and fabrication techniques that offer advantageous characteristics in wound dressing materials is important [8].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of pores www.advancedsciencenews.com www.ms-journal.de or dimples is also due to the combined effect of nature polymer, rate of evaporation of solvent, temperature, etc. [24,25] In the present work, pit or dimple formation is due to the combined effect of moisture, solvent volatility, and non-water-soluble nature of P(VDF-TrFE). P(VDF-TrFE) is a non-water-soluble polymer and methyl ethyl ketone (MEK) is a volatile solvent, the fast evaporation of solvent and water molecule condensation during the elongation of electrospun jet gives dimples or pits on the nanofiber.…”
Section: Esemmentioning
confidence: 78%
“…The formation of pores or dimples is also due to the combined effect of nature polymer, rate of evaporation of solvent, temperature, etc. [ 24,25 ]…”
Section: Resultsmentioning
confidence: 99%
“…The matrix was melt-blended with each of the fillers at the weight percentages shown in Table 15 . Although there are several polymer composites processing technique [8] , [9] , [10] , [11] , the melt-blending technique was used because it is environmentally benign, cost-effective, best for mass production, toxin-free [12] and allows for the addition of higher weight per cent of fillers. The weight per cent formulation of the fillers was obtained from the mass of the fillers ( Table 15 ) according to Eq.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%